Increased sputum peripheral helper T cells are associated with the severity of rheumatoid arthritis but not with the severity of airway disease - Yokoi, Eito; Wakahara, Keiko; Nakamura, Saya; Fukutani, Eriko; Asai, Shuji; Takahashi, Nobunori; Kojima, Toshihisa; Iwano, Shingo; Shimada, Satoko; Chen-Yoshikawa, Toyofumi Fengshi; Hashimoto, Naozumi; Ishii, Makoto (Frontiers in Immunology, 2025)
ObjectivePeripheral helper T (Tph) cells, together with plasma cells, are the major pathogenic lymphocytes in the synovium in rheumatoid arthritis (RA). However, whether these cells are involved in RA-associated lung and/or airway disease is unknown.MethodsTph cells in sputum were analyzed by flow cytometry and compared with those in synovial fluid and synovial tissue. Forty RA subjects for whom induced sputum could be collected were analyzed along with sputum Tph cells and several clinical parameters; RA severity was assessed using the Disease Activity Score for 28 joints (DAS28). Lung and airway disease was assessed by chest computed tomography (CT), pulmonary function test, the chronic obstructive pulmonary disease (COPD) Assessment Test (CAT), and sputum culture. Tph cells in the lung of RA subjects were analyzed using lung resection samples in a separate cohort.ResultsTph cells were observed in the sputum, as well as the lung, synovial fluid, and synovial tissue of RA patients. Sputum Tph cells were increased in patients with airway disease. Among these patients, Tph cells were more frequent in those with high DAS28, high serum immunoglobulin G (IgG), and high sputum IgG. However, there was no association between Tph cells and the severity of airway disease as assessed by chest CT findings, lung function, CAT, and sputum culture.ConclusionsTph cells were increased in the airways as well as in the synovium in patients with RA. Airway Tph cells were associated with severity of RA but not with the severity of airway disease. Airway Tph cells may represent a novel target for disease management and treatment.